b) (- 1/3) ^ 2 + 6 / (- 1/2) + căn (25) – (- 2011) ^ 0

b) (- 1/3) ^ 2 + 6 / (- 1/2) + căn (25) – (- 2011) ^ 0

2 bình luận về “b) (- 1/3) ^ 2 + 6 / (- 1/2) + căn (25) – (- 2011) ^ 0”

  1. Giải đáp+Lời giải và giải thích chi tiết:
    b)(-1/3)^2 +6/(-1/2) +\sqrt{25}-(-2011)^0
    =1/9 +6:(-1/2) +5 -1
    =1/9 -12+4
    =1/9 -8
    =(-71)/9.
     

    Trả lời
  2. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    b,(-1/3)^2 + 6 / (-1/2) + √25 – (-2011)^0
    =1/9 + 6 : (-1/2) + 5 – 1
    =1/9 + (-12) + 5 – 1
    =1/9 + (-7) – 1
    =1/9 + (-8)
    =(-71/9)

    Trả lời

Viết một bình luận

Câu hỏi mới